Simultaneous nitrate and organic matter removal from a dairy effluent by biodenitrification - Hamdani, Ahmed; Mountadar, Mohammed; Assobhei, Omar (Revue des sciences de l’eau / Journal of Water Science)

(untitled) (Université du Québec - INRS-Eau, Terre et Environnement (INRS-ETE), 2018)
In order to study the simultaneous removal of nitrate and organic matter from a dairy effluent containing 670 mg∙L-1 of nitrate (NO3--N) and 5 760 mg∙L-1 of dissolved chemical oxygen demand (CODd), denitrification in a laboratory scale bioreactor consisting of an immersed bacterial bed colonized by an heterotrophic denitrifying flora (HDF) selected for NO3- reduction, COD consumption and adapted to grow on an effluent produced by a dairy industry was investigated. The obtained results indicated that at the optimal conditions of temperature (30°C), pH (7), COD/NO3--N ratio (5), the operation lasted 108h with total reduction of nitrate in 72h, no nitrite accumulation, and 92% of soluble COD removal in 96h. This indicates that the biodenitrification was accompanied with a high efficiency of matter organic removal as an electron donor, and thereby satisfies the applicable standards.